Les terres polonaises de l'ouest - Gruchman, Bohdan; Klafkowski, Alfons; Kolipinski, Juliusz (Poznan : Instytut Zachodni, 1959)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: territoriale kwesties; Polen